Disentangling the effects of dung pat shape and mass on greenhouse gas emissions in the presence of dung beetles - Samantha Bennett; David Burton; Rhea Lumactud; Ghader Manafiazar; Paul Manning (Science of The Total Environment, 2026)

High‐Throughput Sequencing in Aquaculture Disease Investigations: Challenges and Opportunities for Implementation - Francisca Samsing; Phoebe Arbon; Matthew Arnold; Andrew C. Barnes; David Bass; Joy A. Becker; Jerusha Bennett; Charles Caraguel; Jeremy Carson; Vincenzo A. Costa; Thomas Dumond; Jemma Geoghegan; et al. (Reviews in Aquaculture, 2026)
The current generation of sequencing technologies can produce terabases of data with exceptional accuracy and speed, at a fraction of the cost of older methods. Despite this unprecedented power, adoption into aquaculture health management presents several challenges, including identifying where such capability may be optimally deployed. Here we synthesise discussions from a structured expert workshop held at the 2025 Aotearoa Aquatic Diseases Symposium in Dunedin, New Zealand, where experts from industry, government and academia explored the challenges and opportunities for adopting high‐throughput sequencing (HTS) to support disease investigations in aquaculture. Workshop participants identified key applications for HTS, including pathogen discovery during unexplained mortality events and source attribution in epidemics, but also noted technical, regulatory and social challenges for widespread adoption. These include the need for standardised sampling and bioinformatic workflows, data sovereignty, equitable access to the technology and uncertainty around interpreting detection of notifiable pathogens. Targeted research and coordinated regulatory frameworks will be essential to guide responsible use of HTS and determine where it adds value relative to existing approaches. Clarifying these opportunities and constraints will guide the responsible adoption of HTS into aquaculture health management to support sustainable growth for the sector.

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Treatment of post-lung transplantation pneumonia with cefiderocol: a case series and insights from the literature - Gabriele Giuliano; Arianna Lippi; Margherita Sambo; Laerta Dulislami; Marta Zanchi; David Bennett; Antonella Fossi; Alberto Michielon; Daniele Marianello; Antonella Puddu; Chiara Catelli; Piero Paladini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Metabolic cost of external work: a novel CPET parameter optimises characterisation of exercise performance in obese individuals - Jennifer J. Rayner; Rebecca R. Chamley; Robert Barker Davies; Oliver O’Sullivan; Peter Ladlow; Alex N. Bennett; Edward D. Nicol; Oliver J. Rider; David A. Holdsworth (European Journal of Applied Physiology, 2026)
Purpose Both obesity and cardiorespiratory fitness are crucial determinants of symptoms and prognosis. However, interpreting the gold-standard cardiopulmonary exercise test (CPET) is complicated by increasing body size and varying body composition. We hypothesised that the ‘metabolic cost of external work’ (or oxygen uptake (ml/min)/workload (Watts); V̇O 2 /W), a body weight-independent determinant of endurance capacity, would reflect metabolic health more accurately than V̇O 2 alone. Methods A test cohort of 160 fit individuals underwent anthropomorphic and metabolic assessment, maximal bicycle ergometer CPET, and six-minute walk test (6MWT). V̇O 2 /W was calculated at VT1 and peak. The performance of V̇O 2 /W was validated in 62 older, less fit individuals, undergoing the same protocol. 24 obese volunteers were assigned a weight loss intervention, and the impact on V̇O 2 /W examined. Results In both test and validation cohort, V̇O 2 /W at VT1 and peak correlated with 6MWT distance, more strongly than standard CPET parameters. Including V̇O 2 /W improved the accuracy of predicting 6MWT distance. V̇O 2 /W correlated with BMI, insulin sensitivity and waist-to-hip ratio. Metabolic cost falls with weight loss, in parallel to metabolic and functional improvements, in contrast to other CPET parameters. Conclusion Metabolic cost is strongly associated with functional capacity and metabolic health across a range of body weight and fitness, outperforming standard CPET metrics. It is a simple measure which may improve our assessment of the extent to which exertional symptoms are determined by metabolic factors in an individual, and thereby target the most appropriate intervention to those who will benefit most. Graphical Abstract

Acute Toxicity of 6PPDQ, 6PPD, and Other Transformation Products to a Freshwater Mussel (Lampsilis siliquoidea, Barnes 1823) - David J. Soucek; Rebecca A. Dorman; Jeffery A. Steevens; Viviane Yargeau; Marco Pineda; Christopher D. Metcalfe; Erin R. Bennett (Bulletin of Environmental Contamination and Toxicology, 2026)

Molecular taxonomy of the guitarfish genus Acroteriobatus (Rhinopristiformes: Rhinobatidae) - Mia J. Groeneveld; Juliana D. Klein; Michaela van Staden; Rhett H. Bennett; Matthew L. Dicken; David A. Ebert; Bruce Q. Mann; Kashmika Perumal; Ralph G. A. Watson; Aletta E. Bester-van der Merwe (Marine Biodiversity, 2026)
Guitarfish species (genus Acroteriobatus ) display restricted distributions in undermanaged regions of intense fishing pressure. The importance of accurate specimen identification is well established, especially in the context of conservation management. However, guitarfishes remain poorly understood, which is exacerbated by taxonomic uncertainty due to morphological similarity. We therefore aimed (1) to identify molecular operational taxonomic units (MOTUs) within Acroteriobatus by analysing sampled specimens as well as publicly available sequence data for the cytochrome c oxidase subunit I ( COI ) and nicotinamide adenine dehydrogenase subunit 2 (ND2 ) genes, and (2) to augment and review the representation of these sequences on public databases. A molecular taxonomic approach integrating species delimitation and specimen assignment methods revealed 14 MOTUs. These MOTUs aligned with current species descriptions, displaying no evidence of cryptic diversity. Both genes demonstrated similar interspecific relationships that broadly reflected current distribution ranges, underscoring sub-regional endemism. Moreover, discrepancies in public sequence repositories were identified, attributed to misidentified specimens and the usage of outdated taxonomic nomenclature. Genetic diversity indices were substantially inflated when specimens were grouped based on reported species versus delimited MOTUs, thus overestimating genetic diversity. We highlight the need for extensive, curated DNA reference libraries, including revising earlier sequence entries in light of new taxonomic insights, to enable reliable identification of morphologically conserved species. The molecular resolution illustrated in this study can aid in clarifying taxonomic uncertainties in the genus Acroteriobatus .

Craniofacial photography for detection of positional obstructive sleep apnoea - Kate Sutherland; John Wheatley; Kristina Kairaitis; Brendon J. Yee; Gary Cohen; Kerri Melehan; Stephen Lambert; Philip de Chazal; Peter A. Cistulli; Peter Cistulli; Philip de Chazal; Nina Sarkissian; et al. (Sleep and Biological Rhythms, 2026)
Supine-dependent OSA is a well-recognised OSA phenotype and may relate to craniofacial structure. Our aim was to assess whether craniofacial photos are able to identify positional OSA, specifically supine-isolated OSA, in comparison to non-positional OSA. Frontal and profile craniofacial photographs of participants were acquired according to a standardised protocol. Photographs were analysed and compared between non-positional and supine-isolated OSA groups. A total of 156 OSA patients were included (54.5% supine-isolated OSA, 45.5% with non-positional OSA). The supine-isolated group had a longer upper face height and greater upper-to-lower face height ratio, smaller face width, reduced face width-to-height ratio, and smaller mandibular width, length, and size of the mandibular base. Differences in facial measurements were no longer significant after adjustment for body size and OSA severity. Our study demonstrates that supine-isolated OSA can be identified using facial photography. Larger studies in groups matched for BMI and OSA severity are needed to confirm whether this technique may also capture other features related to supine-isolated OSA (i.e., differences in underlying skeletal structure).

Unraveling Aberrant Metabolic Patterns in Alzheimer’s Disease Subtypes: From Perturbed Metabolic Pathways to Candidate Drug Targets - Hatice Büşra Lüleci; Attila Jones; Ryan A. Neff; David A. Bennett; Bin Zhang; Tunahan Çakır; Madhav Thambisetty (Molecular Neurobiology, 2026)

Epistatic effects of IGHG and FCGRIIB genes on the development of Alzheimer’s disease in African Americans - Janardan P. Pandey; Paul J. Nietert; Aryan M. Namboodiri; David A. Bennett; Lisa L. Barnes (Immunogenetics, 2025)
Genome-wide association studies (GWAS) of Alzheimer’s disease (AD) have identified a large number of susceptibility genes, but most of AD heritability remains unexplained, implying the existence of additional genes. Furthermore, the majority of the GWAS have been conducted in people of European descent, and the genes important for AD susceptibility in people of African descent have been underexplored. In this hypothesis-generating prospective cohort study, we genotyped 191 African Americans (AAs) from three longitudinal cohorts on aging for the IgG3 allotype GM6, which is expressed exclusively in people of African descent, and assessed its interaction with IGHG , FCGRIIB , and HLA-DRB1 genes. Cox proportional hazards modeling showed that GM6 by itself was not significantly associated with AD development. However, there was evidence of epistatic interaction: The risk of developing AD associated with GM6 positivity was significantly different ( p = 0.0098) in non-GM17/GM17 participants compared with GM 17/GM17 participants. Specifically, in non-GM17/GM17 participants, the risk of AD was over fourfold higher in GM6-positive participants compared with GM 6-negative participants (HR = 4.63). Similarly, risk of developing AD associated with GM6 positivity was marginally different in non-FCGRIIB TT participants compared with FCGRIIB TT participants. In non-FCGRIIB TT participants, the risk of developing AD was over twofold higher in GM6-positive participants compared with GM6-negative participants (HR = 2.44). This is the first report suggesting that immunoglobulin GM allotypes might play a role in AD etiology among AAs; however, since this was largely a hypothesis-generating study, replication in larger cohorts would be required to confirm this finding.

Accounting for human–nature linkages in area‐based conservation monitoring through social–ecological indicator bundles - Natalie C. Ban; Mark H. Carr; Emily M. Rubidge; Anne Salomon; Joachim Claudet; Arielle Levine; Lindsay Aylesworth; Luisa Ramirez; Jenn M. Burt; Mark Andrachuk; Natascia Tamburello; Rebecca Martone; et al. (Conservation Biology, 2025)
As the coverage of area‐based conservation increases across the globe, it is critical to improve understanding of the social and ecological outcomes of such measures and the pathways to their outcomes. A social–ecological systems approach to monitoring and evaluation is increasingly advocated; yet, applications remain scarce. We sought to facilitate operationalization of this approach through prioritization of indicators when resources are scarce and to improve capture of social–ecological interactions. We convened a working group of practitioners and academics to explore linked social and ecological interactions through a case study of marine protected areas (MPAs). We used causal models (implemented through causal loop diagrams) in participatory and future‐oriented approaches to identify interactions among key nodes of the system that can be a focus of monitoring. These nodes and their interactions provided insight into linked indicators of key system components, for example, biomass, compliance, perceived legitimacy, catches, and perceived fairness. We called these indicator bundles . Indicator bundles can be applied to analyze causal modeling diagrams, identify essential elements to monitor, and inform analytical and reporting protocols. The bundles can also help identify key leverage points for adaptive management to improve outcomes of existing interventions. This approach can inform monitoring and evaluation and, ultimately, the design and adaptive management of conservation areas that maximize social and ecological benefits and minimize negative trade‐offs.

Correction: Positive and negative impacts of electrical infrastructure on animal biodiversity: A systematic review - Adam J. Bennett; David M. Watson; Maggie J. Watson (Oecologia, 2025)

Association between socioeconomic status and dispensing of higher-risk drug classes and polypharmacy in older community-based populations: a nationwide cohort study - Juliane Frydenlund; Nicole Cosgrave; David J. Williams; Frank Moriarty; Emma Wallace; Ciara Kirke; Kathleen Bennett; Caitriona Cahir (European Journal of Clinical Pharmacology, 2025)
Background Higher-risk medications are associated with increased risk of medication-related harm in older populations. Aim To investigate the association between socioeconomic status (SES) and the prescribing of higher-risk drug classes and polypharmacy in older community-dwelling adults. Methods This prospective, population-based cohort study used linked data from the Irish Longitudinal Study on Ageing (TILDA, 2018), the Health Service Executive-Primary Care Reimbursement Service (HSE-PCRS), and the General Medical Services (GMS) scheme over a 2-year follow-up. SES was measured by education, income, and private health insurance. Higher-risk drugs included antithrombotic agents, beta-blockers, calcium channel blockers, diuretics, renin–angiotensin–aldosterone system (RAAS) inhibitors, psychoanaleptics, and NSAIDs. Polypharmacy was categorised as 0–4, 5–9, and 10 + drug classes. Multivariable logistic and ordinal regression models adjusted for age, sex, and multimorbidity were used. Results The study included 1,401 individuals aged ≥ 70 years (median age 79; 43% male); 53% had ≥ 3 chronic conditions. 43% had primary/no education, 46% had below-median income, and 55% lacked private health insurance. Antithrombotics were the most prescribed higher-risk drug (38%), and 41% had 10 + different drug classes. Higher-risk prescribing and polypharmacy were more prevalent in those with lower SES. Participants with low SES were significantly more likely to be prescribed higher-risk drugs and experience polypharmacy. The greatest association was for psychoanaleptics: adjusted OR 1.97 [95% CI: 1.32;2.95] for primary/no formal education vs. third-level education, and 1.73 [95% CI: 1.30;2.30] for no vs. private health insurance. Conclusion SES-related disparities in higher-risk prescribing highlight the need for targeted interventions addressing social determinants of health in older populations.

What is ‘good evidence’ for environmental decision making? Insights from professionals working at the science-policy interface - Elizabeth A. Nyboer; Andrew N. Kadykalo; Nathan Young; Vivian M. Nguyen; Trina Rytwinski; John-Francis Lane; Joseph R. Bennett; Nathan Harron; Susan M. Aitken; Graeme Auld; David Browne; Aerin L. Jacob; et al. (Environmental Science & Policy, 2025)

Calibration of the FullCAM model for Australian native vegetation - David I. Forrester; Jacqueline R. England; Chiara Pasut; Keryn I. Paul; Lauren T. Bennett; Chris Eastaugh; Thomas Fairman; Melissa Fedrigo; Carl R. Gosper; Sabine Kasel; Tom Lewis; Crispen Marunda; et al. (Ecological Modelling, 2025)

Positive and negative impacts of electrical infrastructure on animal biodiversity: A systematic review - Adam J. Bennett; David M. Watson; Maggie J. Watson (Oecologia, 2025)
Electrical infrastructure networks are predicted to greatly expand in response to the expected 48% increase in global energy demand by 2040. While assessments of electrical infrastructure are abundant, mixed effects on animal diversity have been reported, warranting further evaluation to determine true effects. We conducted a systematic literature review covering individual, population, and community-level assessments to determine the impacts posed to animal biodiversity by electrical infrastructure and the measures to reduce impacts. Our results show that the literature around electrical infrastructure and animal biodiversity has grown exponentially since the start of the millennium and is biased towards birds and mammals in economically developed countries. We found the majority of reported impacts were negative, occurring primarily through barrier effects (collision) and use of linear features as a resource (electrocution), causing significant population impacts in select species. However, we also found that electrical infrastructure provided positive effects (increased habitat provisioning) to certain taxonomic groups (e.g. corvids, storks), which suggests the potential to encourage conservation efforts using appropriate mitigation on electrical infrastructure. We found the majority of current literature detailed mitigation measures focused on reducing collisions through line (51%) and tower alterations (30%), but often omitted the impacts of EMF, noise, and UV, indicating significant knowledge gaps. On a wider scale, we found that mortality from electrical infrastructure ranked lower than building collisions and predation from feral cats, but remained higher than other anthropogenic energy sources, indicating the potential to cause significant impacts to large-bodied bird species if not addressed.

Using species distribution modelling in identifying locations for habitat restoration, relocations and potential ecological traps for the sand lizard, Lacerta agilis, in Northern Germany - David Bennett; Tim Diekötter (European Journal of Wildlife Research, 2025)
The sand lizard Lacerta agilis is a species of conservation concern in many areas, primarily due to habitat loss and fragmentation. Wildflower compensation areas, an increasingly widespread method of supporting biodiversity in intensive agricultural landscapes, could theoretically support L. agilis but may also act as an ecological trap. Using species distribution modelling, we estimated the relative habitat suitability for L. agilis across Schleswig Holstein. We then performed field studies at 41 wildflower sites (with varying levels of relative suitability) over two years using reptile mats, and a follow up survey with conservation detection dogs at four more sites. Ultimately, no L. agilis were observed at any site, regardless of method. However, the response curves and variable response curves indicate that permanent semi natural habitat has a strong positive influence on relative suitability. This could indicate that longer term measures are a better option for the conservation of this species.

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Genomic Analysis Reveals a New Cryptic Taxon Within the Anopheles gambiae Complex With a Distinct Insecticide Resistance Profile in the Coast of East Africa - Sophia H. Mwinyi; Kelly L. Bennett; Sanjay C. Nagi; Bilali Kabula; Johnson Matowo; David Weetman; Francesco Baldini; Simon A. Babayan; Martin J. Donnelly; Chris S. Clarkson; Fredros O. Okumu; Alistair Miles (Molecular Ecology, 2025)
Anopheles mosquitoes are major malaria vectors, encompassing several species complexes with diverse life histories, transmission risks and insecticide resistance profiles that challenge malaria control efforts. This study investigated the genetic structure and insecticide resistance profiles of Anopheles gambiae complex mosquitoes in Tanzania. We analysed whole‐genome sequence data of 300 mosquitoes collected between 2012 and 2015 across four regions in northern Tanzania and identified An. gambiae s.s., An. arabiensis and a distinct taxonomic group that was previously unknown. This distinct taxon has a unique profile of genetic diversity and appears restricted to the coastal region, and we refer to it as the Pwani molecular form. Analysis of insecticide resistance based on target‐site mutations and copy number variations (CNV) showed that these markers were strikingly absent from the Pwani molecular form in contrast to other taxa. Our analysis also revealed a pattern of geographical isolation in the An. gambiae s.s. populations, with samples from the north‐western site (Muleba) clustering separately from those collected in the north‐eastern site (Muheza). These geographically isolated subpopulations also had differing resistance and selection profiles, with An. gambiae s.s. from the north‐western site showing genomic evidence of higher resistance to pyrethroids compared with the north‐eastern population. Conversely, An. arabiensis showed no geographical population structuring, with a similar insecticide resistance profile across all sampling locations, suggesting unrestricted gene flow. Our findings underscore the need to incorporate genetic data into malaria vector surveillance and control decisions and could inform the development and deployment of new interventions.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Latitudinal gradients in herbivorous and detritivorous reef fish productivity - Sterling B. Tebbett; Helen F. Yan; Scott Bennett; Graham J. Edgar; Scott D. Ling; Rick D. Stuart-Smith; David R. Bellwood (Reviews in Fish Biology and Fisheries, 2025)

Ocean equity: from assessment to action to improve social equity in ocean governance - Nathan J. Bennett; Veronica Relano; Katina Roumbedakis; Jessica Blythe; Mark Andrachuk; Joachim Claudet; Neil Dawson; David Gill; Natali Lazzari; Shauna L. Mahajan; Ella-Kari Muhl; Maraja Riechers; et al. (Frontiers in Marine Science, 2025)
Inequity is ubiquitous in the ocean, and social equity receives insufficient attention in ocean governance and management efforts. Thus, we assert that proponents of sustainability must center social equity in future ocean governance, to address past social and environmental injustices, to align with international law and conservation policy, and to realize objectives of sustainability. This obligation applies across all marine policy realms, including marine conservation, fisheries management, climate adaptation and the ocean economy, in all socio-political contexts and at different geographical scales. Indeed, many governmental, non-governmental, and philanthropic organizations are striving to advance social equity across their ocean sustainability focused agendas, policies, programs, initiatives, and portfolios. To date, however, there has been limited attention to how to meaningfully assess status and monitor progress on social equity in ocean governance (aka “ocean equity”) across different marine policy realms. Here, we contribute to ongoing efforts to advance ocean equity through providing guidance on five steps to develop bespoke, fit to purpose and contextually appropriate assessment and monitoring frameworks and approaches to measure status of and track changes in ocean equity. These steps include: 1) Clearly articulating the overarching purpose and aim; 2) Convening a participatory group and process to co-design the assessment framework; 3) Identifying important objectives, aspects and attributes of social equity to assess; 4) Selecting and developing indicators, methods, and measures; and 5) Collecting, analyzing and evaluating data. Then, we discuss four subsequent steps to take into account to ensure that assessments lead to adaptations or transformations to improve ocean equity. These steps include: 1) Communicating results to reach key audiences, to enable learning and inform decision-making; 2) Deliberating on actions and selecting interventions to improve ocean equity; 3) Ensuring actions to improve ocean equity are implemented; and, 4) Committing to continual cycles of monitoring, evaluation, learning and adapting at regular intervals. Following these steps could contribute to a change in how oceans are governed. The diligent pursuit of ocean equity will help to ensure that the course towards a sustainable ocean is more representative, inclusive and just.

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Challenges in assessing the effects of environmental governance systems on conservation outcomes - Raphael A. Ayambire; Trina Rytwinski; Jessica J. Taylor; Matthew W. Luizza; Matthew J. Muir; Cynthia Cadet; Derek Armitage; Nathan J. Bennett; Jeremy Brooks; Samantha H. Cheng; Jenny Martinez; Meenakshi Nagendran; et al. (Conservation Biology, 2025)
Effective governance is crucial for the success of conservation projects aimed at protecting wildlife populations and supporting human well‐being. However, few large‐scale, comprehensive syntheses have been conducted on the effects of different environmental governance types on conservation outcomes (i.e., biological and ecological effectiveness or effects of conservation on human well‐being), and clarity on the quantity and quality of evidence remains dispersed and ambiguous. We attempted a systematic map of the evidence on the effectiveness of different governance types to meet desired conservation outcomes in Africa, Asia, and Latin America. However, early in this effort, we observed a general lack of empirical research on the links between governance and conservation outcomes. To fill observed data gaps in the evidence base, we tried triangulating governance data from alternative sources (Protected Planet database) and pooling evidence from research conducted within the same conservation areas. Limited data were contained in the Protected Planet database, and governance types in conservation areas and landscapes were complex, making it difficult to use these approaches to assign governance types to conservation areas. To illustrate our observations from the failed systematic map attempt, we prepared a rapid evidence map that outlines a subset of the evidence base of articles linking governance types and governance principles with conservation outcomes. Only 3.2% (34 of 1067) of the articles we screened directly related conservation outcomes to governance type, and even fewer related governance principles to conservation outcomes. Based on our findings, we recommend improving the evidence base by supporting empirical research and increasing the availability and quality of governance data in freely accessible databases. These recommendations are critical for enhancing understanding of the role of governance in conservation projects and improving conservation outcomes.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Trace metal distribution in seagrass-vegetated sediments of an urbanized estuary in Queensland, Australia - Heera Lee; Clare Morrison; Nicholas J.C. Doriean; David T. Welsh; William W. Bennett (Marine Pollution Bulletin, 2024)

Holobiont Traits Shape Climate Change Responses in Cryptic Coral Lineages - Carsten G. B. Grupstra; Kirstin S. Meyer‐Kaiser; Matthew‐James Bennett; Maikani O. Andres; David J. Juszkiewicz; James E. Fifer; Jeric P. Da‐Anoy; Kelly Gomez‐Campo; Isabel Martinez‐Rugerio; Hannah E. Aichelman; Alexa K. Huzar; Annabel M. Hughes; et al. (Global Change Biology, 2024)
As ocean warming threatens reefs worldwide, identifying corals with adaptations to higher temperatures is critical for conservation. Genetically distinct but morphologically similar (i.e. cryptic) coral populations can be specialized to extreme habitats and thrive under stressful conditions. These corals often associate with locally beneficial microbiota (Symbiodiniaceae photobionts and bacteria), obscuring the main drivers of thermal tolerance. Here, we leverage a holobiont (massive Porites ) with high fidelity for C15 photobionts to investigate adaptive variation across classic (“typical” conditions) and extreme reefs characterized by higher temperatures and light attenuation. We uncovered three cryptic lineages that exhibit limited micro‐morphological variation; one lineage dominated classic reefs (L1), one had more even distributions (L2), and a third was restricted to extreme reefs (L3). L1 and L2 were more closely related to populations ~4300 km away, suggesting that some lineages are widespread. All corals harbored Cladocopium C15 photobionts; L1 and L2 shared a photobiont pool that differed in composition between reef types, yet L3 mostly harbored unique photobiont strains not found in the other lineages. Assemblages of bacterial partners differed among reef types in lineage‐specific ways, suggesting that lineages employ distinct microbiome regulation strategies. Analysis of light‐harvesting capacity and thermal tolerance revealed adaptive variation underpinning survival in distinct habitats: L1 had the highest light absorption efficiency and lowest thermal tolerance, suggesting that it is a classic reef specialist. L3 had the lowest light absorption efficiency and the highest thermal tolerance, showing that it is an extreme reef specialist. L2 had intermediate light absorption efficiency and thermal tolerance, suggesting that is a generalist lineage. These findings reveal diverging holobiont strategies to cope with extreme conditions. Resolving coral lineages is key to understanding variation in thermal tolerance among coral populations, can strengthen our understanding of coral evolution and symbiosis, and support global conservation and restoration efforts.

Differential correlations of changes in in vivo neuroimaging markers of hippocampal volume and arteriolosclerosis with declining financial and health literacy in old age - Lei Yu; Tianhao Wang; Alifiya Kapasi; Melissa Lamar; Gary Mottola; Konstantinos Arfanakis; David A. Bennett; Patricia A. Boyle (Brain Imaging and Behavior, 2024)

Associations between structural neuroimaging markers of Alzheimer’s risk and scam susceptibility - Melissa Lamar; Konstantinos Arfanakis; Alifiya Kapasi; S. Duke Han; David A. Bennett; Lei Yu; Patricia A. Boyle (Brain Imaging and Behavior, 2024)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Longitudinal relationships between depressive symptoms, functional impairment, and physical activity in later late life - Lisa Y. Xiong; Madeline Wood Alexander; Hugo Cogo-Moreira; Che-Yuan Wu; Michael Eid; Nathan Herrmann; Damien Gallagher; Jodi D. Edwards; Krista L. Lanctôt; Susan Marzolini; David A. Bennett; Jennifer S. Rabin; et al. (GeroScience, 2024)

Modelling the spatial abundance of invasive deer and their impacts on vegetation at the landscape scale - Melissa Fedrigo; Ami Bennett; Stephen B. Stewart; David M. Forsyth; Joe Greet (Biological Invasions, 2024)
Deer populations and their impacts on forest ecosystems are increasing globally. Given the imperative and expense to mitigate impacts of invasive deer, we aimed to elucidate critical drivers of (i) deer density, (ii) deer impacts, and (iii) the relationship between them, to facilitate targeted management. We used quantile regression forests to model deer density (faecal pellet counts at 1948 locations) and impacts (browsing and other impacts on > 23,000 woody plants at 343 locations) across a mosaic of agricultural and forested ecosystems in Victoria, Australia (12,775 km 2 ). Climate, topography, vegetation cover, and distance to water features were included as model covariates. Modelled deer density ( r 2 = 0.71, MAE = 0.56 pellets/m 2 ) was most influenced by distance to waterbodies (> 10 ha, 31.2%), elevation (14.3%) and woody vegetation cover (12.9%). Modelled deer impact ( r 2 = 0.32, MAE = 6.9%) was most influenced by deer density (21.0%), mean annual precipitation (12.8%) and elevation (12.2%). Deer density was typically highest near large waterbodies, at low elevation, and with intermediate tree cover (40–70%). Impacts increased steadily with deer density up to ~ 2 pellets/m 2 . Our study demonstrates the importance of forest water and forest agricultural interfaces for both deer density and impacts. Deer are likely to be most abundant near waterbodies due to the availability of high-quality forage and water, and prefer lowland locations that have access to both open and forested habitats. Spatial models can be used to predict deer density and associated impacts to facilitate targeted invasive deer management.

Neglecting hydrological errors can severely impact predictions of water resource system performance - David McInerney; Mark Thyer; Dmitri Kavetski; Seth Westra; Holger R Maier; Margaret Shanafield; Barry Croke; Hoshin Gupta; Bree Bennett; Michael Leonard (Journal of Hydrology, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

A functional perspective on the meaning of the term ‘herbivore’: patterns versus processes in coral reef fishes - Sterling B. Tebbett; Scott Bennett; David R. Bellwood (Coral Reefs, 2024)
Herbivorous fishes are a key functional group in coral reef ecosystems and have been the focus of a vast body of research. While substantial progress has been made in research, challenges persist, especially in respect to quantifying patterns versus processes. Despite this challenge being recognised over 40 years ago. To help clarify such challenges, and work towards solutions, in this perspective we explore how the definition of ‘herbivorous reef fishes’ precludes an easy translation between patterns of herbivore abundance and the process of herbivory. Indeed, if herbivorous fishes are defined as, a fish in which the diet is predominantly based on plant material , then this encompasses a diverse suite of fishes which all remove primary producers to varying extents and have markedly different impacts on reef functioning. Given this situation, we explore how our approaches to directly quantifying herbivory on reefs have progressed. We highlight how lessons learnt from macroalgal assays could be applied to the direct quantification of herbivory from algal turfs in the epilithic algal matrix (EAM); a community of primary producers that are invariably difficult to work with and quantify. Nevertheless, given the abundance of turfs on coral reefs, and their relative importance in herbivore dynamics, widespread process-based assessment of EAM herbivory represents an avenue for expanding future research. Recognising the difficulty of translating patterns in herbivore abundance to the process of herbivory, and an enhanced focus on EAM herbivory, will be necessary to comprehensively quantify the process of herbivory on Anthropocene coral reefs.

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

On-orbit calibration and performance of the EMIT imaging spectrometer - David R. Thompson; Robert O. Green; Christine Bradley; Philip G. Brodrick; Natalie Mahowald; Eyal Ben Dor; Matthew Bennett; Michael Bernas; Nimrod Carmon; K. Dana Chadwick; Roger N. Clark; Red Willow Coleman; et al. (Remote Sensing of Environment, 2024)

Reductive sorption of vanadium by iron monosulfide in seawater - Felicia J. Haase; Colton J. Vessey; Ryo Sekine; Nicholas J.C. Doriean; David T. Welsh; Joseph A. Otte; Jessica Hamilton; Donald E. Canfield; Yun Wang; Enzo Lombi; William W. Bennett (Chemical Geology, 2024)

Lithospheric hydrous pyroxenites control localisation and Ni endowment of magmatic sulfide deposits - Isra S. Ezad; Daryl E. Blanks; Stephen F. Foley; David A. Holwell; Jason Bennett; Marco L. Fiorentini (Mineralium Deposita, 2024)

Elevated pro-inflammatory cytokines and chemokines in saliva of cats with feline odontoclastic resorptive lesion - Sheeba Thomas; David Francis Lappin; David Bennett; Christopher Nile; Marcello Pasquale Riggio (Research in Veterinary Science, 2024)

Characterisation of typical enteropathogenic Escherichia coli (tEPEC) lineages and novel bfpA variants detected in Australian fruit bats (Pteropus poliocephalus) - Fiona McDougall; David Gordon; Roy Robins-Browne; Vicki Bennett-Wood; Wayne S.J. Boardman; Petra L. Graham; Michelle Power (Science of The Total Environment, 2023)

Reductive sorption of vanadium by green rust in seawater - Felicia J. Haase; Colton J. Vessey; Ryo Sekine; David Welsh; Jessica Hamilton; Yun Wang; Jessica White; Donald E. Canfield; Enzo Lombi; William W. Bennett (Geochimica et Cosmochimica Acta, 2023)

A climate stress testing method for changes in spatially variable rainfall - David McInerney; Seth Westra; Michael Leonard; Bree Bennett; Mark Thyer; Holger R. Maier (Journal of Hydrology, 2023)

Metals in coastal seagrass habitats: A systematic quantitative literature review - Heera Lee; Clare Morrison; Nicholas J. C. Doriean; David T. Welsh; William W. Bennett (Critical Reviews in Environmental Science and Technology, 2023)

Evolution of the Palaeozoic mafic-ultramafic Lizard Complex (SW England) from zircon and baddeleyite U-Pb-Hf isotopic constraints: New thoughts on the convergence of Avalonia and Armorica - Allen P. Nutman; Vickie C. Bennett; David H. Green; Clark R.L. Friend (Lithos, 2023)

A legal assessment of private land conservation in South America - Rocío López de la Lama; Nathan Bennett; Janette Bulkan; David Boyd; Kai M. A. Chan (Conservation Biology, 2023)
Privately protected areas (PPAs) are a potentially innovative conservation tool. Legal recognition is necessary for their success, especially where there are institutional challenges to nature conservation, such as in South America. Although PPAs have increased in South America since the early 2000s, there is a critical information gap pertaining to their legal frameworks. We analyzed the level of landowner commitment to and governmental support for PPAs across countries in South America that officially recognize PPAs. We analyzed the legal framework governing PPAs and reviewed literature on them. This process was done in English and Spanish. The information we gathered was validated by 16 conservation experts from 10 South American countries. Because Peru is 1 of only 2 South American countries where local communities create and manage PPAs, we studied Peruvian PPAs in more detail by examining official creation documents and interviewing 13 local conservation professionals. We found inadequate minimum duration of PPAs and vague guidelines for conducting economic activities within them and a lack of governmental support (e.g., financial and technical support) for PPAs. Support was limited to the exemption from rural property taxes, which are relatively low compared with countries outside South America. In Peru, PPAs run by individuals and communities needed different legal frameworks because they were created with different objectives and had different sizes and duration of commitments. The prompt improvement of legal frameworks across South America is necessary for PPAs to achieve their aim of being places for enduring nature conservation in the region.

Building cyberinfrastructure for the reuse and reproducibility of complex hydrologic modeling studies - Iman Maghami; Ashley Van Beusekom; Lauren Hay; Zhiyu Li; Andrew Bennett; YoungDon Choi; Bart Nijssen; Shaowen Wang; David Tarboton; Jonathan L. Goodall (Environmental Modelling & Software, 2023)

Recent Douglas-fir Mortality in the Klamath Mountains Ecoregion of Oregon: Evidence for a Decline Spiral - Max Bennett; David C Shaw; Laura Lowrey (Journal of Forestry, 2023)
Recent increases in Douglas-fir (Psuedotsuga menziesii var. menziesii) mortality in the Klamath Mountains ecoregion raise concerns about the long-term resilience of Douglas-fir in the ecoregion and increased potential for uncharacteristic wildfire. We used data from the USDA Forest Service Aerial Detection Survey and ninety-six field plots to explore the relationships between physiographic and climate variables and Douglas-fir mortality. Our results provide strong evidence for a decline spiral in which Douglas-fir growing on hot, dry sites (predisposing factor) are further stressed by drought (inciting factor) and are then exploited by the flatheaded fir borer (Phaenops drummondi) and other secondary biotic agents (contributing factors), resulting in decline and mortality. At the landscape scale, Douglas-fir mortality increased as average annual precipitation declined and average climatic water deficit increased. We developed a risk score integrating several environmental variables associated with drought and heat stress to predict the likelihood and intensity of mortality at the stand scale.

Investing in nature-based solutions: Cost profiles of collective-action watershed investment programs - Shiteng Kang; Timm Kroeger; Daniel Shemie; Marta Echavarria; Tamara Montalvo; Leah L. Bremer; Genevieve Bennett; Samuel Roiphe Barreto; Henrique Bracale; Claudia Calero; Aldo Cardenas; Julián Cardona; et al. (Ecosystem Services, 2023)

Synthetic microbial consortia bioprocessing integrated with pyrolysis for efficient conversion of cellulose to valuables - Chandrakant Joshi; Mahesh Kumar; Martyn Bennett; Jyotika Thakur; David J. Leak; Swati Sharma; Neil MacKinnon; Shyam Kumar Masakapalli (Bioresource Technology Reports, 2023)

Dose metric evaluation of a cell-based bioassay for assessing the toxicity of metals to Dugong dugon: Effect of metal-media interactions on exposure concentrations - David Bailey; Kimberly A. Finlayson; Gulsah Dogruer; William W. Bennett; Jason P. van de Merwe (Aquatic Toxicology, 2023)

Angiotensin receptor blocker use is associated with upregulation of the memory-protective angiotensin type 4 receptor (AT4R) in the postmortem brains of individuals without cognitive impairment - Caglar Cosarderelioglu; Lolita S. Nidadavolu; Claudene J. George; Ruth Marx-Rattner; Laura Powell; Qian-Li Xue; Jing Tian; Esther S. Oh; Luigi Ferrucci; Pervin Dincer; David A. Bennett; Jeremy D. Walston; et al. (GeroScience, 2023)

Environmental (in)justice in the Anthropocene ocean - Nathan J. Bennett; Juan José Alava; Caroline E. Ferguson; Jessica Blythe; Elisa Morgera; David Boyd; Isabelle M. Côté (Marine Policy, 2023)

Historic palaeobotanical collection reveals in situ microspores and pollen from Early Carboniferous (Tournaisian) ovules from the Ballagan Formation of Scotland - Emma Reeves; John E.A. Marshall; Carys Bennett; Sarah Davies; Timothy Kearsey; David Millward (Review of Palaeobotany and Palynology, 2023)

Vulnerable Waters are Essential to Watershed Resilience - Charles R. Lane; Irena F. Creed; Heather E. Golden; Scott G. Leibowitz; David M. Mushet; Mark C. Rains; Qiusheng Wu; Ellen D’Amico; Laurie C. Alexander; Genevieve A. Ali; Nandita B. Basu; Micah G. Bennett; et al. (Ecosystems, 2023)
Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

The P2X1 receptor as a therapeutic target - Felix M. Bennetts; Jesse I. Mobbs; Sabatino Ventura; David M. Thal (Purinergic Signalling, 2022)
Within the family of purinergic receptors, the P2X1 receptor is a ligand-gated ion channel that plays a role in urogenital, immune and cardiovascular function. Specifically, the P2X1 receptor has been implicated in controlling smooth muscle contractions of the vas deferens and therefore has emerged as an exciting drug target for male contraception. In addition, the P2X1 receptor contributes to smooth muscle contractions of the bladder and is a target to treat bladder dysfunction. Finally, platelets and neutrophils have populations of P2X1 receptors that could be targeted for thrombosis and inflammatory conditions. Drugs that specifically target the P2X1 receptor have been challenging to develop, and only recently have small molecule antagonists of the P2X1 receptor been available. However, these ligands need further biological validation for appropriate selectivity and drug-like properties before they will be suitable for use in preclinical models of disease. Although the atomic structure of the P2X1 receptor has yet to be determined, the recent discovery of several other P2X receptor structures and improvements in the field of structural biology suggests that this is now a distinct possibility. Such efforts may significantly improve drug discovery efforts at the P2X1 receptor.

A simplified gravitational reference sensor for satellite geodesy - Anthony Dávila Álvarez; Aaron Knudtson; Unmil Patel; Joseph Gleason; Harold Hollis; Jose Sanjuan; Neil Doughty; Glenn McDaniel; Jennifer Lee; James Leitch; Stephen Bennett; Riccardo Bevilacqua; et al. (Journal of Geodesy, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

The cost of avoiding predators: a bioenergetic analysis of diel vertical migration by the opossum shrimp Mysis diluviana - Steven R. Chipps; David H. Bennett; David Deslauriers; Lars G. Rudstam (Hydrobiologia, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Integrating Biophysical, Socio-Economic and Governance Principles Into Marine Reserve Design and Management in Mexico: From Theory to Practice - Magdalena Précoma-de la Mora; Nathan J. Bennett; Stuart Fulton; Adrian Munguia-Vega; Cristina Lasch-Thaler; Mariana Walther-Mendoza; José Alberto Zepeda-Domínguez; Elena Marie Finkbeiner; Alison L. Green; Alvin Suárez; Amy Hudson Weaver; Ana Luisa R. Figueroa Carranza; et al. (Frontiers in Marine Science, 2021)
Marine conservation design and fisheries management are increasingly integrating biophysical, socio-economic and governance considerations. Integrative approaches are adopted to achieve more effective, equitable, inclusive, and robust marine policies and practices. This paper describes a participatory process to co-produce biophysical, socio-economic, and governance principles to guide the design and management of marine reserves in three regions of Mexico: the Pacific region of the Baja California Peninsula, the Gulf of California, and the Mexican Caribbean. The process of co-producing the principles included convening a coordination team, reviewing the science, convening multi-stakeholder workshops, developing and communicating the principles with key practitioners and policy makers, and supporting uptake and application to policy and practice. Biophysical principles were related to: habitat representation and risk spreading; protecting critical, special and unique areas; incorporating connectivity; allowing time for recovery; adapting to changes in climate and ocean chemistry; and considering threats and opportunities. Socio-economic principles focused on: integrating the social context, local aspirations, and human-environment interactions; considering economic and non-economic uses, promoting an equitable distribution of costs and benefits, and respecting and maintaining cultural identity and diversity. Governance principles prioritized establishing and ensuring legitimacy and institutional continuity; implementing collaborative and adaptive management; and, promoting effective management. The paper also examines early efforts to implement the principles, next steps to promote further uptake and application in Mexico, and lessons learned from the process. Thus it provides insights into a practical process and a set of principles that are valuable to inform marine conservation and fisheries management processes elsewhere.

Distribution and volume analysis of early hemorrhagic contusions by MRI after traumatic brain injury: a preliminary report of the Epilepsy Bioinformatics Study for Antiepileptogenic Therapy (EpiBioS4Rx) - Marianna La Rocca; Giuseppe Barisano; Alexis Bennett; Rachael Garner; Jerome Engel; Emily J. Gilmore; David L. McArthur; Eric Rosenthal; James Stanis; Paul Vespa; Frederick Willyerd; Lara L. Zimmermann; et al. (Brain Imaging and Behavior, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Altered structure of bat–prey interaction networks in logged tropical forests revealed by metabarcoding - David R. Hemprich‐Bennett; Victoria A. Kemp; Joshua Blackman; Matthew J. Struebig; Owen T. Lewis; Stephen J. Rossiter; Elizabeth L. Clare (Molecular Ecology, 2021)
Habitat degradation is pervasive across the tropics and is particularly acute in Southeast Asia, with major implications for biodiversity. Much research has addressed the impact of degradation on species diversity; however, little is known about how ecological interactions are altered, including those that constitute important ecosystem functions such as consumption of herbivores. To examine how rainforest degradation alters trophic interaction networks, we applied DNA metabarcoding to construct interaction networks linking forest‐dwelling insectivorous bat species and their prey, comparing old‐growth forest and forest degraded by logging in Sabah, Borneo. Individual bats in logged rainforest consumed a lower richness of prey than those in old‐growth forest. As a result, interaction networks in logged forests had a less nested structure. These network structures were associated with reduced network redundancy and thus increased vulnerability to perturbations in logged forests. Our results show how ecological interactions change between old‐growth and logged forests, with potentially negative implications for ecosystem function and network stability.

Distribution modelling of the garden dormouse Eliomys quercinus (Linnaeus, 1766) with novel climate change indicators - David Bennett; Freddie Jeanne Richard (Mammalian Biology, 2021)
The garden dormouse Eliomys quercinus has been declining in both abundance and range since the mid-twentieth century. The eastern edge of its range has contracted from the Ural Mountains to eastern Germany. Habitat loss and fragmentation has been the most supported theory to explain the observed decline. Climate change has been implicated in declines of other terrestrial mammals, but not investigated for E. quercinus . To better understand the factors influencing the distribution of this species and to map habitat suitability for E. quercinus across Europe, we created a Maxent species distribution model. Among the main environmental variables used for the modelling, two novel climate change indicator variables were produced to indicate the degree of climate change between the early twentieth century and the present. Areas of high suitability were mapped, and variable importance estimated using jackknife tests and variable contribution metrics. The climate change indicators outperformed many conventional variables, which could indicate that climate change is a factor behind the current distribution of E. quercinus . We also analysed the land use types where presence points of E. quercinus were located and whether they were in areas of “high nature value farmland”. Over 30% of all spatially filtered presence points corresponded to high nature value farmland areas. Our results could indicate a role for changing climate (particularly in temperature) in the range decline E. quercinus , and for high nature value farmland practices in conserving this species. Field studies and improved monitoring for this species are recommended to confirm both possible findings.

Conservation resource allocation, small population resiliency, and the fallacy of conservation triage - David A. Wiedenfeld; Allison C. Alberts; Ariadne Angulo; Elizabeth L. Bennett; Onnie Byers; Topiltzin Contreras‐MacBeath; Gláucia Drummond; Gustavo A. B. da Fonseca; Claude Gascon; Ian Harrison; Nicolas Heard; Axel Hochkirch; et al. (Conservation Biology, 2021)
Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss.

Limited Progress in Improving Gender and Geographic Representation in Coral Reef Science - Gabby N. Ahmadia; Samantha H. Cheng; Dominic A. Andradi-Brown; Stacy K. Baez; Megan D. Barnes; Nathan J. Bennett; Stuart J. Campbell; Emily S. Darling; Estradivari; David Gill; Erika Gress; Georgina G. Gurney; et al. (Frontiers in Marine Science, 2021)
Despite increasing recognition of the need for more diverse and equitable representation in the sciences, it is unclear whether measurable progress has been made. Here, we examine trends in authorship in coral reef science from 1,677 articles published over the past 16 years (2003–2018) and find that while representation of authors that are women (from 18 to 33%) and from non-OECD nations (from 4 to 13%) have increased over time, progress is slow in achieving more equitable representation. For example, at the current rate, it would take over two decades for female representation to reach 50%. Given that there are more coral reef non-OECD countries, at the current rate, truly equitable representation of non-OECD countries would take even longer. OECD nations also continue to dominate authorship contributions in coral reef science (89%), in research conducted in both OECD (63%) and non-OECD nations (68%). We identify systemic issues that remain prevalent in coral reef science (i.e., parachute science, gender bias) that likely contribute to observed trends. We provide recommendations to address systemic biases in research to foster a more inclusive global science community. Adoption of these recommendations will lead to more creative, innovative, and impactful scientific approaches urgently needed for coral reefs and contribute to environmental justice efforts.

Self-reported experiences of discrimination in older black adults are associated with insula functional connectivity - S. Duke Han; Melissa Lamar; Debra Fleischman; Namhee Kim; David A. Bennett; Tené T. Lewis; Konstantinos Arfanakis; Lisa L. Barnes (Brain Imaging and Behavior, 2021)

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

Pandora: 4-D White Matter Bundle Population-Based Atlases Derived from Diffusion MRI Fiber Tractography - Colin B Hansen; Qi Yang; Ilwoo Lyu; Francois Rheault; Cailey Kerley; Bramsh Qamar Chandio; Shreyas Fadnavis; Owen Williams; Andrea T. Shafer; Susan M. Resnick; David H. Zald; Laurie E Cutting; et al. (Neuroinformatics, 2021)

Education in Ecological Engineering—a Need Whose Time Has Come - Glenn Dale; Gabriela Dotro; Puneet Srivastava; David Austin; Stacy Hutchinson; Peter Head; Ashantha Goonetilleke; Alexandros Stefanakis; Ranka Junge; José A. Fernández L.; Vanessa Weyer; Wayne Truter; et al. (Circular Economy and Sustainability, 2021)
Overcoming Limitations of Ecology and Engineering in Addressing Society’s Challenges By providing an integrated, systems-approach to problem-solving that incorporates ecological principles in engineering design, ecological engineering addresses, many of the limitations of Ecology and Engineering needed to work out how people and nature can beneficially coexist on planet Earth. Despite its origins in the 1950s, ecological engineering remains a niche discipline, while at the same time, there has never been a greater need to combine the rigour of engineering and science with the systems-approach of ecology for pro-active management of Earth’s biodiversity and environmental life-support systems. Broad consensus on the scope and defining elements of ecological engineering and development of a globally consistent ecological engineering curriculum are key pillars to mainstream recognition of the discipline and practice of ecological engineering. The Importance of Ecological Engineering in Society In this paper, the importance of ecological engineering education is discussed in relation to the perceived need of our society to address global challenges of sustainable development. The perceived needs of industry, practitioners, educators and students for skills in ecological engineering are also discussed. The Importance and Need for Ecological Engineering Education The need for integrative, interdisciplinary education is discussed in relation to the scope of ecology, engineering and the unique role of ecological engineering. Scope for a Universally Recognised Curriculum in Ecological Engineering The scope for a universally recognised curriculum in ecological engineering is presented. The curriculum recognises a set of overarching principles and concepts that unite multiple application areas of ecological engineering practice. The integrative, systems-based approach of ecological engineering distinguishes it from the trend toward narrow specialisation in education. It is argued that the systems approach to conceptualising problems of design incorporating ecological principles is a central tenant of ecological engineering practice. Challenges to Wider Adoption of Ecological Engineering and Opportunities to Increase Adoption Challenges and structural barriers to wider adoption of ecological engineering principles, embedded in our society’s reliance on technological solutions to environmental problems, are discussed along with opportunities to increase adoption of ecological engineering practice. It is suggested that unifying the numerous specialist activity areas and applications of ecological engineering under an umbrella encompassing a set of core principles, approaches, tools and way of thinking is required to distinguish ecological engineering from other engineering disciplines and scale up implementation of the discipline. It is concluded that these challenges can only be realised if ecological engineering moves beyond application by a relatively small band of enthusiastic practitioners, learning by doing, to the education of future cohorts of students who will become tomorrow’s engineers, project managers, procurement officers and decision makers, applying principles informed by a growing body of theory and knowledge generated by an active research community, a need whose time has come, if we are to deploy all tools at our disposal toward addressing the grand challenge of creating a sustainable future.

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

Assessing the impact of taxon resolution on network structure - David R. Hemprich‐Bennett; Hernani F. M. Oliveira; Steven C. Le Comber; Stephen J. Rossiter; Elizabeth L. Clare (Ecology, 2021)
Constructing ecological networks has become an indispensable approach in understanding how different taxa interact. However, the methods used to generate data in network research vary widely among studies, potentially limiting our ability to compare results meaningfully. In particular, methods of classifying nodes vary in their precision, likely altering the architecture of the network studied. For example, rather than being classified as Linnaean species, taxa are regularly assigned to morphospecies in observational studies, or to molecular operational taxonomic units (MOTUs) in molecular studies, with the latter defined based on an arbitrary threshold of sequence similarity. Although the use of MOTUs in ecological networks holds great potential, especially for allowing rapid construction of large data sets of interactions, it is unclear how the choice of clustering threshold can influence the conclusions obtained. To test the impact of taxonomic precision on network architecture, we obtained and analyzed 16 data sets of ecological interactions, inferred from metabarcoding and observations. Our comparisons of networks constructed under a range of sequence thresholds for assigning taxa demonstrate that even small changes in node resolution can cause wide variation in almost all key metric values. Moreover, relative values of commonly used metrics such as robustness were seen to fluctuate continuously with node resolution, thereby potentially causing error in conclusions drawn when comparing multiple networks. In observational networks, we found that changing node resolution could, in some cases, lead to substantial changes to measurements of network topology. Overall, our findings highlight the importance of classifying nodes to the greatest precision possible, and demonstrate the need for caution when comparing networks that differ with respect to node resolution, even where taxonomic groups and interaction types are similar. In such cases, we recommend that comparisons of networks should focus on relative differences rather than absolute values between the networks studied.

Range extension of the Critically Endangered shorttail nurse shark Pseudoginglymostoma brevicaudatum (Orectolobiformes: Ginglymostomatidae) to include Mozambique, with implications for management - Rhett H. Bennett; David A. Ebert; Jorge J. Sitoe; Stela Fernando; Mark Harris; David van Beuningen; Aseeqah Davids (Marine Biodiversity, 2021)

White matter correlates of scam susceptibility in community-dwelling older adults - Melissa Lamar; Konstantinos Arfanakis; Lei Yu; Shengwei Zhang; S. Duke Han; Debra A. Fleischman; David A. Bennett; Patricia A. Boyle (Brain Imaging and Behavior, 2020)

The pregnancy microbiome and preterm birth - Erna Bayar; Phillip R. Bennett; Denise Chan; Lynne Sykes; David A. MacIntyre (Seminars in Immunopathology, 2020)
Preterm birth is a global health concern and continues to contribute to substantial neonatal morbidity and mortality despite advances in obstetric and neonatal care. The underlying aetiology is multi-factorial and remains incompletely understood. In this review, the complex interplay between the vaginal microbiome in pregnancy and its association with preterm birth is discussed in depth. Advances in the study of bacteriology and an improved understanding of the human microbiome have seen an improved awareness of the vaginal microbiota in both health and in disease.

The COVID-19 Pandemic, Small-Scale Fisheries and Coastal Fishing Communities - Nathan J. Bennett; Elena M. Finkbeiner; Natalie C. Ban; Dyhia Belhabib; Stacy D. Jupiter; John N. Kittinger; Sangeeta Mangubhai; Joeri Scholtens; David Gill; Patrick Christie (Coastal Management, 2020)

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

Resistance of soil biota and plant growth to disturbance increases with plant diversity - Jonathan A. Bennett; Alexander M. Koch; Jennifer Forsythe; Nancy C. Johnson; David Tilman; John Klironomos (Ecology Letters, 2020)
Plant diversity is critical to the functioning of ecosystems, potentially mediated in part by interactions with soil biota. Here, we characterised multiple groups of soil biota across a plant diversity gradient in a long‐term experiment. We then subjected soil samples taken along this gradient to drought, freezing and a mechanical disturbance to test how plant diversity affects the responses of soil biota and growth of a focal plant to these disturbances. High plant diversity resulted in soils that were dominated by fungi and associated soil biota, including increased arbuscular mycorrhizal fungi and reduced plant‐feeding nematodes. Disturbance effects on the soil biota were reduced when plant diversity was high, resulting in higher growth of the focal plant in all but the frozen soils. These results highlight the importance of plant diversity for soil communities and their resistance to disturbance, with potential feedback effects on plant productivity.

Gene expression and DNA methylation are extensively coordinated with MRI-based brain microstructural characteristics - Chris Gaiteri; Robert Dawe; Sara Mostafavi; Katherine D. Blizinsky; Shinya Tasaki; Vitalina Komashko; Lei Yu; Yanling Wang; Julie A. Schneider; Konstantinos Arfanakis; Philip L. De Jager; David A. Bennett (Brain Imaging and Behavior, 2019)

Sex Differences in Gene and Protein Expression After Intracerebral Hemorrhage in Mice - Yongqiu Xie; Yi-Ju Li; Beilei Lei; Dawn Kernagis; Wen-Wei Liu; Ellen R. Bennett; Talagnair Venkatraman; Christopher D. Lascola; Daniel T. Laskowitz; David S. Warner; Michael L. James (Translational Stroke Research, 2019)

White matter correlates of temporal discounting in older adults - S. Duke Han; Konstantinos Arfanakis; Debra A. Fleischman; Lei Yu; David A. Bennett; Patricia A. Boyle (Brain Structure and Function, 2018)

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Elucidating the sponge stress response; lipids and fatty acids can facilitate survival under future climate scenarios - Holly Bennett; James J. Bell; Simon K. Davy; Nicole S. Webster; David S. Francis (Global Change Biology, 2018)
Ocean warming ( OW ) and ocean acidification ( OA ) are threatening coral reef ecosystems, with a bleak future forecast for reef‐building corals, which are already experiencing global declines in abundance. In contrast, many coral reef sponge species are able to tolerate climate change conditions projected for 2100. To increase our understanding of the mechanisms underpinning this tolerance, we explored the lipid and fatty acid ( FA ) composition of four sponge species with differing sensitivities to climate change, experimentally exposed to OW and OA levels predicted for 2100, under two CO 2 Representative Concentration Pathways. Sponges with greater concentrations of storage lipid, phospholipids, sterols and elevated concentrations of n ‐3 and n ‐6 long‐chain polyunsaturated FA ( LC PUFA ), were more resistant to OW . Such biochemical constituents likely contribute to the ability of these sponges to maintain membrane function and cell homeostasis in the face of environmental change. Our results suggest that n ‐3 and n ‐6 LC PUFA are important components of the sponge stress response potentially via chain elongation and the eicosanoid stress‐signalling pathways. The capacity for sponges to compositionally alter their membrane lipids in response to stress was also explored using a number of specific homeoviscous adaptation ( HVA ) indicators. This revealed a potential mechanism via which additional CO 2 could facilitate the resistance of phototrophic sponges to thermal stress through an increased synthesis of membrane‐stabilizing sterols. Finally, OW induced an increase in FA unsaturation in phototrophic sponges but a decrease in heterotrophic species, providing support for a difference in the thermal response pathway between the sponge host and the associated photosymbionts. Here we have shown that sponge lipids and FA are likely to be an important component of the sponge stress response and may play a role in facilitating sponge survival under future climate conditions.

Neutron and X-ray total scattering study of hydrogen disorder in fully hydrated hydrogrossular, Ca3Al2(O4H4)3 - David A. Keen; Dean S. Keeble; Thomas D. Bennett (Physics and Chemistry of Minerals, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Distributional responses to marine heat waves: insights from length frequencies across the geographic range of the endemic reef fish Choerodon rubescens - Katherine Cure; Jean-Paul A. Hobbs; Timothy J. Langlois; David A. Abdo; Scott Bennett; Euan S. Harvey (Marine Biology, 2018)

Genome-Wide Association Analysis of the Sense of Smell in U.S. Older Adults: Identification of Novel Risk Loci in African-Americans and European-Americans - Jing Dong; Annah Wyss; Jingyun Yang; T. Ryan Price; Aude Nicolas; Michael Nalls; Greg Tranah; Nora Franceschini; Zongli Xu; Claudia Schulte; Alvaro Alonso; Steven R. Cummings; et al. (Molecular Neurobiology, 2017)

Trace metal content in inhalable particulate matter (PM2.5–10 and PM2.5) collected from historical mine waste deposits using a laboratory-based approach - Rachael Martin; Kim Dowling; Dora C. Pearce; Singarayer Florentine; Stafford McKnight; Eduard Stelcer; David D. Cohen; Attila Stopic; John W. Bennett (Environmental Geochemistry and Health, 2017)

Balancing generality and specificity in ecological gradient analysis with species abundance distributions and individual size distributions - Jian D. L. Yen; James R. Thomson; Jonathan M. Keith; David M. Paganin; Erica Fleishman; David S. Dobkin; Joanne M. Bennett; Ralph Mac Nally (Global Ecology and Biogeography, 2017)
Aim Data on ecological communities are often condensed into single‐valued diversity indices, which support comparisons among ecosystems but may discard important information. At the other extreme, some studies retain full data on the identities of all species present, which retains maximum information on community structure but occludes comparisons among ecosystems. We sought to determine whether the analysis of species abundance distributions and individual size distributions could support more detailed inferences than diversity indices while remaining sufficiently general to identify fundamental ecological responses in multiple ecosystems. Location The United States and south‐eastern Australia. Methods We analysed changes in species abundance distributions and individual size distributions along environmental gradients. We compared analyses of distributions with analyses of five diversity indices and with a distance‐based multivariate analysis of species composition. We used data from 1438 fish communities in the United States and from 840 bird communities in the western United States and south‐eastern Australia. These communities were sampled over 10–20 years and included 298 species of birds and 488 species of fishes. Results Analyses of species abundance distributions and individual size distributions identified environmental associations that were not found in analyses of diversity indices, and revealed common associations with shrubs in bird communities on different continents and with temperature in communities of birds and fishes. Individual size distributions were associated more closely with environmental variables than were species abundance distributions. Main conclusions Our novel identification of ecological associations suggests that analyses of community distributions might reveal fundamental ecological processes common to multiple ecosystems. Close associations between individual sizes and environmental variables suggest that a greater focus on size in ecological analyses might assist in the development of general models of ecological communities.

Tissue Transglutaminase and Its Product Isopeptide Are Increased in Alzheimer’s Disease and APPswe/PS1dE9 Double Transgenic Mice Brains - Ji Zhang; Suqing Wang; Wei Huang; David A. Bennett; Dennis W. Dickson; Dengshun Wang; Rui Wang (Molecular Neurobiology, 2016)

Design and Verification of Novel Low-Cost MR-Guided Small-Animal Stereotactic System - Jonathan D. Plasencia; Leland S. Hu; Gregory H. Turner; Kevin M. Bennett; David H. Frakes (Journal of Medical and Biological Engineering, 2016)

Grey matter correlates of susceptibility to scams in community-dwelling older adults - S. Duke Han; Patricia A. Boyle; Lei Yu; Konstantinos Arfanakis; Bryan D. James; Debra A. Fleischman; David A. Bennett (Brain Imaging and Behavior, 2016)

Cognitive activity, cognitive function, and brain diffusion characteristics in old age - Konstantinos Arfanakis; Robert S. Wilson; Christopher M. Barth; Ana W. Capuano; Anil Vasireddi; Shengwei Zhang; Debra A. Fleischman; David A. Bennett (Brain Imaging and Behavior, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Potentially inappropriate prescribing in two populations with differing socio-economic profiles: a cross-sectional database study using the PROMPT criteria - Janine A. Cooper; Frank Moriarty; Cristín Ryan; Susan M. Smith; Kathleen Bennett; Tom Fahey; Emma Wallace; Caitriona Cahir; David Williams; Mary Teeling; Carmel M. Hughes (European Journal of Clinical Pharmacology, 2016)

Association of white matter hyperintensities and gray matter volume with cognition in older individuals without cognitive impairment - Zoe Arvanitakis; Debra A. Fleischman; Konstantinos Arfanakis; Sue E. Leurgans; Lisa L. Barnes; David A. Bennett (Brain Structure and Function, 2016)

Biofilm formation in an experimental water distribution system: the contamination of non-touch sensor taps and the implication for healthcare - Ginny Moore; David Stevenson; Katy-Anne Thompson; Simon Parks; Didier Ngabo; Allan M. Bennett; Jimmy T. Walker (Biofouling, 2015)

GSK3β Interactions with Amyloid Genes: An Autopsy Verification and Extension - Timothy J. Hohman; Lori Chibnik; William S. Bush; Angela L. Jefferson; Phillip L. De Jaeger; Tricia A. Thornton-Wells; David A. Bennett; Julie A. Schneider (Neurotoxicity Research, 2015)

The Relationship Between Sap Flow and Commercial Soil Water Sensor Readings in Irrigated Potato (Solanum tuberosum L.) Production - Seth A. Byrd; Diane L. Rowland; Jerry Bennett; Lincoln Zotarelli; David Wright; Ashok Alva; John Nordgaard (American Journal of Potato Research, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Keeping qRT-PCR rigorous and biologically relevant - John Bennett; David Hondred; James C. Register (Plant Cell Reports, 2015)

Gray-matter macrostructure in cognitively healthy older persons: associations with age and cognition - Debra A. Fleischman; Sue Leurgans; Konstantinos Arfanakis; Zoe Arvanitakis; Lisa L. Barnes; Patricia A. Boyle; S. Duke Han; David A. Bennett (Brain Structure and Function, 2014)

Impact of fresh root material and mature crop residues of oilseed rape (Brassica napus) on microbial communities associated with subsequent oilseed rape - Amanda J. Bennett; Sally Hilton; Gary D. Bending; David Chandler; Peter Mills (Biology and Fertility of Soils, 2014)

Validating DICOM Transcoding with an Open Multi-Format Resource - Benjamin C. Yvernault; Charles D. Theobald; Jolinda C. Smith; Victoria Villalta; David H. Zald; Bennett A. Landman (Neuroinformatics, 2014)

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Characterizing microbial communities and processes in a modern stromatolite ( S hark B ay) using lipid biomarkers and two‐dimensional distributions of porewater solutes - Anais Pagès; Kliti Grice; Michael Vacher; David T. Welsh; Peter R. Teasdale; William W. Bennett; Paul Greenwood (Environmental Microbiology, 2014)
Summary Modern microbial mats are highly complex and dynamic ecosystems. Diffusive equilibration in thin films ( DET ) and diffusive gradients in thin films ( DGT ) samplers were deployed in a modern smooth microbial mat from Shark Bay in order to observe, for the first time, two‐dimensional distributions of porewater solutes during day and night time. Two‐dimensional sulfide and alkalinity distributions revealed a strong spatial heterogeneity and a minor contribution of sulfide to alkalinity. Phosphate distributions were also very heterogeneous, while iron( II ) distributions were quite similar during day and night with a few hotspots of mobilization. Lipid biomarkers from the three successive layers of the mat were also analysed in order to characterize the microbial communities regulating analyte distributions. The major hydrocarbon products detected in all layers included n ‐alkanes and isoprenoids, whilst other important biomarkers included hopanoids. Phospholipid fatty acid profiles revealed a decrease in cyanobacterial markers with depth, whereas sulfate‐reducing bacteria markers increased in abundance in accordance with rising sulfide concentrations with depth. Despite the general depth trends in community structure and physiochemical conditions within the mat, two‐dimensional solute distributions showed considerable small‐scale lateral variability, indicating that the distributions and activities of the microbial communities regulating these solute distributions were equally heterogeneous and complex.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Performance of an empirical bias‐correction of a high‐resolution climate dataset - James C. Bennett; Michael R. Grose; Stuart P. Corney; Christopher J. White; Gregory K. Holz; Jack J. Katzfey; David A. Post; Nathaniel L. Bindoff (International Journal of Climatology, 2014)
We describe the method and performance of a bias‐correction applied to high‐resolution (˜10 km) simulations from a stretched‐grid Regional Climate Model ( RCM ) over Tasmania, Australia. The bias‐correction is a quantile mapping of empirical cumulative frequency distributions. Corrections are applied at a daily time step to five variables: rainfall, potential evaporation (PE), solar radiation, maximum temperature and minimum temperature. Corrections are calculated independently for each season. We show that quantile mapping of empirical distributions can be highly effective in correcting biases in RCM outputs. Cross‐validation shows biases are effectively reduced across the range of cumulative frequency distributions, with few exceptions. The bias‐correction is not as effective at correcting biases for values at or near zero (e.g. in rainfall simulations), although even here the bias‐correction improves biases evident in the uncorrected simulations. In addition, the bias‐correction improves frequency characteristics of variables such as the number of rain days. We use a detrending technique to apply the bias‐correction to 140‐year time series of RCM variables. We show that the bias‐correction effectively preserves long‐term changes (e.g. to the mean and variance) to variables projected by the uncorrected RCM simulations. Correlations between key variables are also largely preserved, thus the bias‐corrected outputs reflect the dynamics of the underlying RCM . However, the bias‐corrected simulations still exhibit some of the deficiencies of the RCM simulations, e.g. the tendency to underestimate the magnitude and duration of large, multi‐day rain events, and the tendency to underestimate the duration of dry spells. The bias‐corrected simulations for six downscaled GCMs for the A2 and B1 emissions scenarios are available to researchers from http://www.tpac.org.au .

Conflicting values: ecosystem services and invasive tree management - Ian A. Dickie; Brett M. Bennett; Larry E. Burrows; Martin A. Nuñez; Duane A. Peltzer; Annabel Porté; David M. Richardson; Marcel Rejmánek; Philip W. Rundel; Brian W. van Wilgen (Biological Invasions, 2014)

A population-based study of dosing and persistence with anti-dementia medications - Linda Brewer; Kathleen Bennett; Cora McGreevy; David Williams (European Journal of Clinical Pharmacology, 2013)

Implications for Future Survival of Delta Smelt from Four Climate Change Scenarios for the Sacramento–San Joaquin Delta, California - Larry R. Brown; William A. Bennett; R. Wayne Wagner; Tara Morgan-King; Noah Knowles; Frederick Feyrer; David H. Schoellhamer; Mark T. Stacey; Michael Dettinger (Estuaries and Coasts, 2013)

Novel Mutations Mapping to the Fourth Sodium Channel Domain of Nav1.7 Result in Variable Clinical Manifestations of Primary Erythromelalgia - Roman Cregg; Bisola Laguda; Robert Werdehausen; James J. Cox; John E. Linley; Juan D. Ramirez; Istvan Bodi; Michael Markiewicz; Kevin J. Howell; Ya-Chun Chen; Karen Agnew; Henry Houlden; et al. (NeuroMolecular Medicine, 2013)

Prenatal tobacco exposure predicts differential brain function during working memory in early adolescence: a preliminary investigation - David S. Bennett; Feroze B. Mohamed; Dennis P. Carmody; Muhammed Malik; Scott H. Faro; Michael Lewis (Brain Imaging and Behavior, 2013)

Hybrid mouse diversity panel: a panel of inbred mouse strains suitable for analysis of complex genetic traits - Anatole Ghazalpour; Christoph D. Rau; Charles R. Farber; Brian J. Bennett; Luz D. Orozco; Atila van Nas; Calvin Pan; Hooman Allayee; Simon W. Beaven; Mete Civelek; Richard C. Davis; Thomas A. Drake; et al. (Mammalian Genome, 2012)

TOMM40 in Cerebral Amyloid Angiopathy Related Intracerebral Hemorrhage: Comparative Genetic Analysis with Alzheimer’s Disease - Valerie Valant; Brendan T. Keenan; Christopher D. Anderson; Joshua M. Shulman; William J. Devan; Alison M. Ayres; Kristin Schwab; Joshua N. Goldstein; Anand Viswanathan; Steven M. Greenberg; David A. Bennett; Philip L. De Jager; et al. (Translational Stroke Research, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

MRI Shows a Region-Specific Pattern of Atrophy in Spinocerebellar Ataxia Type 2 - Brian C. Jung; Soo I. Choi; Annie X. Du; Jennifer L. Cuzzocreo; Howard S. Ying; Bennett A. Landman; Susan L. Perlman; Robert W. Baloh; David S. Zee; Arthur W. Toga; Jerry L. Prince; Sarah H. Ying (The Cerebellum, 2012)

Perils of correlating CUSUM‐transformed variables to infer ecological relationships (Breton et al. 2006; Glibert 2010) - James E. Cloern; Alan D. Jassby; Jacob Carstensen; William A. Bennett; Wim Kimmerer; Ralph Mac Nally; David H. Schoellhamer; Monika Winder (Limnology and Oceanography, 2012)

Cerebral White Matter Integrity and Cognitive Aging: Contributions from Diffusion Tensor Imaging - David J. Madden; Ilana J. Bennett; Allen W. Song (Neuropsychology Review, 2009)

The role of surface energy and water wettability in aminoalkyl/fluorocarbon/hydrocarbon-modified xerogel surfaces in the control of marine biofouling - Stephanie M. Bennett; John A. Finlay; Nikhil Gunari; David D. Wells; Anne E. Meyer; Gilbert C. Walker; Maureen E. Callow; James A. Callow; Frank V. Bright; Michael R. Detty (Biofouling, 2009)

Cigarette smoking, body mass index, gastro-esophageal reflux disease, and non-steroidal anti-inflammatory drug use and risk of subtypes of esophageal and gastric cancers by P53 overexpression - Jonine D. Figueroa; Mary Beth Terry; Marilie D. Gammon; Thomas L. Vaughan; Harvey A. Risch; Fang-Fang Zhang; David E. Kleiner; William P. Bennett; Christine L. Howe; Robert Dubrow; Susan T. Mayne; Joseph F. Fraumeni; et al. (Cancer Causes & Control, 2009)

Chinese herbal medicine for Mild Cognitive Impairment and Age Associated Memory Impairment: a review of randomised controlled trials - Brian H. May; Angela W. H. Yang; Anthony L. Zhang; Michael D. Owens; Louise Bennett; Richard Head; Lynne Cobiac; Chun Guang Li; Helmut Hugel; David F. Story; Charlie C. L. Xue (Biogerontology, 2009)

Global biogeography and ecology of body size in birds - Valérie A. Olson; Richard G. Davies; C. David L. Orme; Gavin H. Thomas; Shai Meiri; Tim M. Blackburn; Kevin J. Gaston; Ian P. F. Owens; Peter M. Bennett (Ecology Letters, 2009)
In 1847, Karl Bergmann proposed that temperature gradients are the key to understanding geographic variation in the body sizes of warm‐blooded animals. Yet both the geographic patterns of body‐size variation and their underlying mechanisms remain controversial. Here, we conduct the first assemblage‐level global examination of ‘Bergmann’s rule’ within an entire animal class. We generate global maps of avian body size and demonstrate a general pattern of larger body sizes at high latitudes, conforming to Bergmann’s rule. We also show, however, that median body size within assemblages is systematically large on islands and small in species‐rich areas. Similarly, while spatial models show that temperature is the single strongest environmental correlate of body size, there are secondary correlations with resource availability and a strong pattern of decreasing body size with increasing species richness. Finally, our results suggest that geographic patterns of body size are caused both by adaptation within lineages, as invoked by Bergmann, and by taxonomic turnover among lineages. Taken together, these results indicate that while Bergmann’s prediction based on physiological scaling is remarkably accurate, it is far from the full picture. Global patterns of body size in avian assemblages are driven by interactions between the physiological demands of the environment, resource availability, species richness and taxonomic turnover among lineages.

The dapE-encoded N-succinyl-l,l-diaminopimelic acid desuccinylase from Haemophilus influenzae contains two active-site histidine residues - Danuta M. Gillner; David L. Bienvenue; Boguslaw P. Nocek; Andrzej Joachimiak; Vincentos Zachary; Brian Bennett; Richard C. Holz (JBIC Journal of Biological Inorganic Chemistry, 2009)

Regional variation in the historical components of global avian species richness - Gavin H. Thomas; C. David L. Orme; Richard G. Davies; Valerie A. Olson; Peter M. Bennett; Kevin J. Gaston; Ian P. F. Owens; Tim M. Blackburn (Global Ecology and Biogeography, 2008)
Aim Using a global data base of the distribution of extant bird species, we examine the evidence for spatial variation in the evolutionary origins of contemporary avian diversity. In particular, we assess the possible role of the timing of mountain uplift in promoting diversification in different regions. Location Global. Methods We mapped the distribution of avian richness at four taxonomic levels on an equal‐area 1° grid. We examined the relationships between richness at successive taxonomic levels (e.g. species richness vs. genus richness). We mapped the residuals from linear regressions of these relationships to identify areas that are exceptional in the number of lower taxa relative to the number of higher taxa. We use generalized least squares models to test the influence of elevation range and temperature on lower‐taxon richness relative to higher‐taxon richness. Results Peaks of species richness in the Neotropics were congruent with patterns of generic richness, whilst peaks in Australia and the Himalayas were congruent with patterns of both genus and family richness. Hotspots in the Afrotropics did not reflect higher‐taxon patterns. Regional differences in the relationship between richness at successive taxonomic levels revealed variation in patterns of taxon co‐occurrence. Species and genus co‐occurrence was positively associated with elevational range across much of the world. Taxon occurrence in the Neotropics was associated with a positive interaction between elevational range and temperature. Conclusions These results demonstrate that contemporary patterns of richness show different associations with higher‐taxon richness in different regions, which implies that the timing of historical effects on these contemporary patterns varies across regions. We suggest that this is due to dispersal limitation and phylogenetic constraints on physiological tolerance limits promoting diversification. We speculate that diversification rates respond to long‐term changes in the Earth's topography, and that the role of tropical mountain ranges is implicated as a correlate of contemporary diversity, and a source of diversification across avian evolutionary history.

Structure and metal binding properties of ZnuA, a periplasmic zinc transporter from Escherichia coli - Liliya A. Yatsunyk; J. Allen Easton; Lydia R. Kim; Stacy A. Sugarbaker; Brian Bennett; Robert M. Breece; Ivan I. Vorontsov; David L. Tierney; Michael W. Crowder; Amy C. Rosenzweig (JBIC Journal of Biological Inorganic Chemistry, 2008)

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

Hunting for Consensus: Reconciling Bushmeat Harvest, Conservation, and Development Policy in West and Central Africa - ELIZABETH L. BENNETT; ERIC BLENCOWE; KATRINA BRANDON; DAVID BROWN; ROBERT W. BURN; GUY COWLISHAW; GLYN DAVIES; HOLLY DUBLIN; JULIA E. FA; E. J. MILNER‐GULLAND; JOHN G. ROBINSON; J. MARCUS ROWCLIFFE; et al. (Conservation Biology, 2007)

Contaminants in tilapia (Oreochromis mossambicus) from the Salton Sea, California, in relation to human health, piscivorous birds and fish meal production - Marie F. Moreau; Janie Surico-Bennett; Marie Vicario-Fisher; David Crane; Russel Gerads; Richard M. Gersberg; Stuart H. Hurlbert (Hydrobiologia, 2007)

Energy, range dynamics and global species richness patterns: reconciling mid‐domain effects and environmental determinants of avian diversity - David Storch; Richard G. Davies; Samuel Zajíček; C. David L. Orme; Valerie Olson; Gavin H. Thomas; Tzung‐Su Ding; Pamela C. Rasmussen; Robert S. Ridgely; Peter M. Bennett; Tim M. Blackburn; Ian P. F. Owens; et al. (Ecology Letters, 2006)
Spatial patterns of species richness follow climatic and environmental variation, but could reflect random dynamics of species ranges (the mid‐domain effect, MDE). Using data on the global distribution of birds, we compared predictions based on energy availability (actual evapotranspiration, AET, the best single correlate of avian richness) with those of range dynamics models. MDE operating within the global terrestrial area provides a poor prediction of richness variation, but if it operates separately within traditional biogeographic realms, it explains more global variation in richness than AET. The best predictions, however, are given by a model of global range dynamics modulated by AET, such that the probability of a range spreading into an area is proportional to its AET. This model also accurately predicts the latitudinal variation in species richness and variation of species richness both within and between realms, thus representing a compelling mechanism for the major trends in global biodiversity.

Kinetic and spectroscopic characterization of the E134A- and E134D-altered dapE-encoded N-succinyl-l,l-diaminopimelic acid desuccinylase from Haemophilus influenzae - Ryan Davis; David Bienvenue; Sabina I. Swierczek; Danuta M. Gilner; Lakshman Rajagopal; Brian Bennett; Richard C. Holz (JBIC Journal of Biological Inorganic Chemistry, 2006)

(2R,7S)-Diacetoxytridecane: Sex Pheromone of the Aphidophagous Gall Midge, Aphidoletes aphidimyza - Man-Young Choi; Grigori Khaskin; Regine Gries; Gerhard Gries; Bernard D. Roitberg; David A. Raworth; Doo-Ho Kim; Robb G. Bennett (Journal of Chemical Ecology, 2004)

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)

Using Spatially Explicit Data to Evaluate Marine Protected Areas for Abalone in Southern California - Laura Rogers‐Bennett; Peter L. Haaker; Konstantin A. Karpov; David J. Kushner (Conservation Biology, 2002)
Abalone populations have declined dramatically in southern California. The white abalone ( Haliotis sorenseni ) is now ( 2001) on the federal endangered species list. To aid in the restoration of white, pink ( H. corrugata ), and green abalone ( H. fulgens ), productive marine protected areas need to be selected. We used spatially explicit fishery data (1950–1995) to identify the most productive marine areas in southern California. To assess the role of existing marine protected areas we compared fishery‐independent data (1983–2001) inside protected and fished areas. San Clemente Island produced the greatest cumulative catches of white, pink, and green abalone, the most white abalone per hectare of deep reef (25–65 m), and the most green abalone per kilometer of rocky shoreline. Santa Barbara Island, however, produced 10 times more pink abalone per hectare of kelp canopy, making this area an excellent candidate for restoration and protection. Pink abalone surveyed in the Kelp Forest Monitoring Program were most abundant at three sites surrounding Anacapa Island: (1) protected, (2) protected but less visible, and (3) fished. The protected sites, despite having lower abundances of pink abalone initially (1983), had significantly more abalone ( H = 9.0; df = 2; p = 0.011) than the nearby fished site over time. Size‐frequency distributions revealed that the protected site had more (30%) commercial‐size abalone (≥158 mm shell length) than the less visable site (6%) or the fished site (2%). Mean size was significantly larger at the protected site, yielding the highest estimate of biomass and potential egg production (2555 million eggs/site/year) of all the sites. Marine protected areas need to be selected and enforced so that abalone‐restoration efforts can be enacted before remnant populations die. Restoration sites for a wide variety of depleted species can be selected based on previous levels of productivity identified by spatially explicit data.

Serotonin in cisternal cerebrospinal fluid of rhesus monkeys: basal levels and effects of sertraline administration - George Anderson; Allyson Bennett; Katherine Weld; Judy Pushkas; David Ocame; Dee Higley (Psychopharmacology, 2002)

Dog MHC alleles containing the human RA shared epitope confer susceptibility to canine rheumatoid arthritis - William Ollier; Lorna Kennedy; Wendy Thomson; Annette Barnes; Susan Bell; David Bennett; John Angles; John Innes; Stuart Carter (Immunogenetics, 2001)

Evaluating Nonpoint Pollution Policy Using a Tightly Coupled Spatial Decision Support System - DAVID A. BENNETT; ANDREW J. VITALE (Environmental Management, 2001)

BETR North America: A regionally segmented multimedia contaminant fate model for North America - Matthew MacLeod; David G. Woodfine; Donald Mackay; Tom McKone; Deborah Bennett; Randy Maddalena (Environmental Science and Pollution Research, 2001)

Land-Use Dynamics in a Southern Illinois (USA) Watershed - CHRISTOPHER LANT; TIMOTHY LOFTUS; STEVEN KRAFT; DAVID BENNETT (Environmental Management, 2001)

Discriminating the role of binocular information in the timing of a one-handed catch - Simon J. Bennett; John van der Kamp; Geert J. P. Savelsbergh; Keith Davids (Experimental Brain Research, 2000)

Non-erythroid form of acute intermittent porphyria caused by promoter and frameshift mutations distant from the coding sequence of exon 1 of the HMBS gene - Sharon D. Whatley; Andrew G. Roberts; David H. Llewellyn; Christopher P. Bennett; Christine Garrett; George H. Elder (Human Genetics, 2000)

Managing the Koala Problem: Interdisciplinary Perspectives - Elaine Stratford; Nicole Mazur; Daniel Lunney; David Bennett (Conservation Biology, 2000)
There is a complex scientific, ethical, and cultural debate in Australia about how best to conserve koalas and their habitat. Despite the diverse array of management and research options promoted by scientists, wildlife agency staff, and koala advocates, there remains a gap in our acknowledgment of the social factors influencing decision making about koala conservation. Koala management research has generated valuable scientific knowledge about koala biology and ecology but has been weak about organizational and policy processes and about the cultures within which we produce, disseminate, and legitimize this kind of knowledge. We suggest that more effective koala conservation will result from making the political and cultural influences on decision making regarding the koala more explicit in research, management, and policy‐making forums. Research must be conducted in the context of the cultural significance of the koala. The koala's survival depends on preserving the valuable lands that these creatures (and many others) inhabit. Ultimately, the koala symbolizes conflicting land‐use values and illustrates the need for greater collaboration, cooperation, and trust among social and natural scientists in the conduct of koala conservation research, management, and policy.

Antitumor efficacy of regional oncolytic viral therapy for peritoneally disseminated cancer - Joseph J. Bennett; David A. Kooby; Keith Delman; Priscilla McAuliffe; Marc W. Halterman; Howard Federoff; Yuman Fong (Journal of Molecular Medicine, 2000)

Preparation of radiolabelled very-low-density lipoprotein in high yield by extended rat liver perfusion - Mark J. Bennett; David Hauton; David G. Hole; Rhys D. Evans (Biotechnology Letters, 2000)

Antisense suppression of tomato endo-1,4-β-glucanase Cel2 mRNA accumulation increases the force required to break fruit abscission zones but does not affect fruit softening - David A. Brummell; Bradford D. Hall; Alan B. Bennett (Plant Molecular Biology, 1999)

Strophanthidin-induced gain of Ca 2+ occurs during diastole and not systole in guinea-pig ventricular myocytes - Deborah L. Bennett; Stephen C. O'Neill; David A. Eisner (Pflügers Archiv - European Journal of Physiology, 1999)

Glacigenic clast fabrics: genetic fingerprint or wishful thinking? - Matthew R. Bennett; Richard I. Waller; Neil F. Glasser; Michael J. Hambrey; David Huddart (Journal of Quaternary Science, 1999)

Nine new dog DLA-DRB1 alleles identified by sequence-based typing - L. J. Kennedy; Stuart D. Carter; Annette Barnes; Susan Bell; David Bennett; William E. R. Ollier; Wendy Thomson (Immunogenetics, 1998)

Cloning, Sequence, and Expression of the Phosphofructokinase Gene of Clostridium acetobutylicum ATCC 824 in Escherichia coli - Ed Belouski; David E. Watson; George N. Bennett (Current Microbiology, 1998)

The Carstairs Kames (Lanarkshire, Scotland): morphology, sedimentology and formation - David Huddart; Matthew R. Bennett (Journal of Quaternary Science, 1997)

The Carstairs Kames (Lanarkshire, Scotland): morphology, sedimentology and formation - David Huddart; Matthew R. Bennett (Journal of Quaternary Science, 1997)

Perceptions of Species Abundance, Distribution, and Diversity: Lessons from Four Decades of Sampling on a Government-Managed Reserve - J. Whitfield Gibbons; Vincent J. Burke; Jeffrey E. Lovich; Raymond D. Semlitsch; Tracey D. Tuberville; J. Russell Bodie; Judith L. Greene; Peter H. Niewiarowski; Howard H. Whiteman; David E. Scott; Joseph H. K. Pechmann; Christopher R. Harrison; et al. (Environmental Management, 1997)

An endo-1,4-β-glucanase expressed at high levels in rapidly expanding tissues - David A. Brummell; Colin R. Bird; Wolfgang Schuch; Alan B. Bennett (Plant Molecular Biology, 1997)

MUC1 gene polymorphism and gastric cancer–an epidemiological study - F Carvalho; R Seruca; L David; A Amorim; M Seixas; E Bennett; H Clausen; M Sobrinho-Simoes (Glycoconjugate Journal, 1997)

The formation of a geometrical ridge network by the surge‐type glacier Kongsvegen, Svalbard - MATTHEW R. BENNETT; MICHAEL J. HAMBREY; DAVID HUDDART; JEAN FRANÇOIS GHIENNE (Journal of Quaternary Science, 1996)

The formation of a geometrical ridge network by the surge-type glacier Kongsvegen, Svalbard - MATTHEW R. BENNETT; MICHAEL J. HAMBREY; DAVID HUDDART; JEAN FRANÇOIS GHIENNE (Journal of Quaternary Science, 1996)

Influence of autoregressive model parameter uncertainty on spectral estimates of heart rate dynamics - David J. Christini; Abhijit Kulkarni; Srikar Rao; Eric R. Stutman; Frederick M. Bennett; Jeffrey M. Hausdorff; Nancy Oriol; Kenneth R. Lutchen (Annals of Biomedical Engineering, 1995)